Coals transportation's steep route to realization - Septiawan, Muhammad; Yanti, Illy; Hartono, Sigit (Sustainability (STPP) Theory, Practice and Policy, 2021)
This research is motivated by the unrealized specific road for transporting coal mining products in Jambi Province which has been delayed for 9 years. This study uses a qualitative research approach. The data sources used in the study were selected by purposive sampling method. The results showed that the construction of a specific road for coal transportation in Jambi Province had not yet had an impact on people's lives. These impacts are economic, social and road safety impacts. The unrealized policy is caused by several factors including the budget, political pressure, the complexity of licensing, and the dynamics of land acquisition.